Individual difference in thermal comfort: A literature review - Wang, Zhe; de Dear, Richard; Luo, Maohui; Lin, Borong; He, Yingdong; Ghahramani, Ali; Zhu, Yingxin (Building and environment, 2018)
Human individual differences widely and markedly affect thermal comfort and should be carefully considered in the design and operation of the built environment. This paper aims to list and examine the magnitude and significance of individual difference in the preferred/neutral/comfort temperature through reviewing previous climate chamber and field studies. Causal factors for individual differences are investigated, including sex, age and etc. There is no clear and consistent conclusions as to the significance and size of inter-group differences in thermal comfort (between females and males, or the young and the old). To address the issue of individual difference, a paradigm shift from centralized to personalized air condition is on the way with the following three steps: first, collecting individual physiological and psychological response; second, predict individual comfort with machine learning algorithms; and third, accommodating individual difference with Personalized Comfort Systems.